Association of air pollution sources and aldehydes with biomarkers of blood coagulation, pulmonary inflammation, and systemic oxidative stress - Altemose, B.; Robson, M. G.; Kipen, H. M.; Strickland, P. O.; Meng, Q. Y.; Gong, J. C.; Huang, W.; Wang, G. F.; Rich, D. Q.; T. Zhu; Zhang, J. F. (Journal of Exposure Science and Environmental Epidemiology, 2017)
Using data collected before, during, and after the 2008 Summer Olympic Games in Beijing, this study examines associations between biomarkers of blood coagulation (vWF, sCD62P and sCD40L), pulmonary inflammation (EBC pH, EBC nitrite, and eNO), and systemic oxidative stress (urinary 8-OHdG) with sources of air pollution identified utilizing principal component analysis and with concentrations of three aldehydes of health concern. Associations between the biomarkers and the air pollution source types and aldehydes were examined using a linear mixed effects model, regressing through seven lag days and controlling for ambient temperature, relative humidity, gender, and day of week for the biomarker measurements. The biomarkers for pulmonary inflammation, particularly EBC pH and eNO, were most consistently associated with vehicle and industrial combustion, oil combustion, and vegetative burning. The biomarkers for blood coagulation, particularly vWF and sCD62p, were most consistently associated with oil combustion. Systemic oxidative stress biomarker (8-OHdG) was most consistently associated with vehicle and industrial combustion. The associations of the biomarkers were generally not significant or consistent with secondary formation of pollutants and with the aldehydes. The findings support policies to control anthropogenic pollution sources rather than natural soil or road dust from a cardio-respiratory health standpoint.
Keywords: air pollution; aldehydes; cardiac autonomic control; cardiorespiratory biomarkers; case-crossover analysis; coronary-artery-disease; exhaled breath condensate; fine particulate matter; healthy-young adults; heart-rate-variability; hospital admissions; implantable cardioverter-defibrillators; myocardial-infarction; olympics; pollutant sources; principal component analysis